Monetary policy transmission in the Euro area : a study by the Eurosystem Monetary Transmission Network - Angeloni, Ignazio; Kashyap, A. K.; Mojon, Benoît.; Eurosystem Monetary Transmission Network (Cambridge ; New York : Cambridge University Press, 2003)
Monetary Policy Transmission in the Euro Area puts together an unprecedented set of studies on the transmission of monetary policy. It covers both the euro area as a whole and the components countries, using aggregate and individual data on firms and banks. The book also demonstrates the great potential synergy existing in the Euro system.
Includes bibliographical references and index.
gau 24/06/14; nmn 27/05/15
Loans
Keywords: Monetary policy; Transmission mechanism (Monetary policy); Euro